Modelling variation of needle density of Scots pine at high latitudes - Salminen, Hannu; Jalkanen, Risto (Silva Fennica, 2006)
The relationship between apical extension and needle density and the effect of temperature and precipitation on needle density was modelled using data gathered from forty-nine felled sample trees in five stands of Scots pine (Pinus sylvestris L.) located along a latitudinal transect from the Arctic Circle up to the northern timberline. The lengths were measured and needle densities assessed from all annual shoots located above 1.3 metres using the Needle Trace Method (NTM), resulting, on average, in 39-year-long chronologies. The mean overall needle density was 7.8 short shoots per shoot centimetre. Needle-density variation in the measured data was mostly due to within-tree differences. Of the total variance, within-tree variation yielded 46%, between-tree 21%, and between-year 27%. The dependence of needle density on annual height growth was studied by fitting a multilevel model with random stand-, tree- and year-intercepts, the independent variables being tree age and height growth. There was a very strong negative correlation between height growth and needle density, and the proportion of between-year variance explained solely by height growth and age was 50%. The stand-wise residual variations and their correlations with the temperature and precipitation time series were further analysed with cross-correlation analysis in order to screen for additional independent variables. The only possible additional independent variable found was the precipitation of AprilâMay (precipitation of May in the two northernmost stands). When it was added to the multi-level model, the proportion of explained between-year needle-density variance was 55%, but the overall fit of the model improved only slightly. The effect of late winter and early spring precipitation indicates the role of snow coverage and snowmelt on the growing conditions in the three southernmost stands. In general, stand-level needle-density variation is mostly due to changes in height growth.